A stitch in time: revolutionizing cancer care in Pakistan - Haseeb Ur Rehman; Hamza Naeem; Ariba Shamsher (Journal of the Pakistan Medical Association, 2024)
Madam, Pakistan is a developing country in South Asia with a young population. According to the International Agency for Research on Cancer, more than 178,000 new cancer patients are diagnosed in Pakistan each year, and the number of people that die from cancer is more than 117,000 per annum. [1]. Most cancer patients in Pakistan present when they are in the advanced stage of their disease. It makes it far more difficult to help the patients rendering efforts at complete cure futile.[1]. One of the leading causes of late identification of cancer is a lack of awareness of cancer as a possible diagnosis, even among physicians, followed by poverty and a lack of basic education and facilities. Pakistan, being a developing country, is facing cancer treatment as a major issue. There are less than 40 hospitals nationwide that claim to provide cancer treatment and facilities for cancer patients [1]. The lack of formal cancer referral channels in Pakistan's health system is a serious problem. This means that patients with suspected cancer may not receive timely diagnosis and treatment. Therefore, it is necessary to introduce a referral pathway like the one used by NICE (National Institute of Health and Care Excellence) for suspected cancer recognition and referral as shown in figure 1 [2]. The importance of cancer referral pathways lies in their ability to facilitate early diagnosis of cancer. Early diagnosis is critical for improving patient outcomes and increasing survival rates. A cohort study on the English urgent referral pathway identified a subgroup of 37% of patients with a low propensity to use urgent referral. Patients with these practices had 7% higher mortality rate compared to the patients having access to urgent cancer referrals. The absolute difference in cumulative mortality was about 5% to 6% in the risk of death four years after the diagnosis of cancer [3]. In the United Kingdom, a formal cancer referral pathway has been put in place to guarantee that patients with suspected cancer receive prompt diagnoses and treatments. Guidelines for referral of suspected cancer have been issued by the National Institute for Health and Care Excellence (NICE). [4] It describes proper primary care investigations and whom to refer for a specialist's opinion. It attempts to inform people about what to anticipate if they experience symptoms that could be cancer.[4] Unfortunately, in Third World countries like Pakistan, there is no such formal pathway. ---Continue